2011
DOI: 10.1088/0022-3727/44/29/295201
|View full text |Cite
|
Sign up to set email alerts
|

Separation of VUV/UV photons and reactive particles in the effluent of a He/O2atmospheric pressure plasma jet

Abstract: Cold atmospheric pressure plasmas can be used for treatment of living tissues or for inactivation of bacteria or biological macromolecules. The treatment is usually characterized by a combined effect of UV and VUV radiation, reactive species, and ions. This combination is usually beneficial for the effectiveness of the treatment but it makes the study of fundamental interaction mechanisms very difficult. Here we report on an effective separation of VUV/UV photons and heavy reactive species in the effluent of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 32 publications
(59 reference statements)
2
37
0
Order By: Relevance
“…Schneider et al observed similar large, disk‐shape inactivation patterns in a μ‐APPJ ignited in a He/O 2 mixture . Measurements using molecular beam mass spectrometry revealed significantly high production of O and O 3 by the μ‐APPJ with O 2 added.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Schneider et al observed similar large, disk‐shape inactivation patterns in a μ‐APPJ ignited in a He/O 2 mixture . Measurements using molecular beam mass spectrometry revealed significantly high production of O and O 3 by the μ‐APPJ with O 2 added.…”
Section: Resultsmentioning
confidence: 84%
“…Measurements using molecular beam mass spectrometry revealed significantly high production of O and O 3 by the μ‐APPJ with O 2 added. Therefore, the inactivation of E. coli at large distances from the jet axis was attributed to O 3 because of its rather long life time …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contemporary, a widely accepted assumption concerning the biological CAP-mediated mechanisms is the occurrence of reactive oxygen and nitrogen species (ROS, RNS) [Bekeschus et al, 2014;Weiss et al, 2015b]. ROS and RNS are only two factors among various biologically reactive particles in the highly reactive-ionized gas, further containing ions, electrons, excited atoms and molecules, free radicals, photons, and electromagnetic fields, subsequently emitting visible ultraviolet, vacuum-ultraviolet, and infra-red radiation [Ahn et al, 2011;Heinlin et al, 2011;Schneider et al, 2011]. CAP treatment of biological tissues and cells becomes feasible due to CAP can be operated at 37-38˚C.…”
Section: Introductionmentioning
confidence: 99%
“…[1]- [3] (cold treatment means that the average gas temperature in plasma jet at the target is close to room temperature). NTP itself is a gaseous mixture containing wide spectrum of biochemically active agents, specific types of which depend on plasma-forming gas mixture.…”
Section: Introductionmentioning
confidence: 99%